Floral fusion à la fibonacci - Jutta, Mariam (University Putra Malaysia, 2012)
Pineapple, a strange name given to a curious plant European explorer first discovered in the Americas in 1664. More appropriate is the Tupi Indian ‘anana’ meaning ‘superior fruit’ from which the Malay nenas and German “Ananas” may originate. This fruit conforms only in part with the way fruits usually develop. Here the whole inflorescence plus the central plant axis form a fleshy multiple pseudocarp or coenocarpium